Obesidad un factor de riesgo para el desarrollo del síndrome de ovarios poliquísticos. - Becerra Quevedo, Karen Denisse (2017)
Polycystic ovary syndrome has developed through history, becoming a multisystem disorder that affects women in all areas. The present investigation consisted of determining obesity as a risk factor for the development of polycystic ovarian syndrome, a descriptive, descriptive, retrospective study was carried out to determine the prevalence of obesity in women of childbearing age between 15-45 years, to identify the prevalence of polycystic ovarian syndrome according to the age group and finally the body mass index and the degree of obesity of the patients of health centers N ° 1, N ° 2, N ° 3 of the city of Loja, period 2010-2015, Where the universe and sample were 50 women of childbearing age with a diagnosis of polycystic ovarian syndrome, the data were obtained from the medical records for which a data collection sheet prepared by the author was used. The results were tabulated in the Microsoft Excel program and presented in tables and bar charts, the processing of the information allowed to determine that the greater prevalence of the syndrome is found in young women between the 15 and 20 years, obesity was present in 26% (n = 13) of women with polycystic ovary syndrome, the most frequent body mass index was 30 kg / m2 with 10% (n = 5) and the most frequent degree of obesity was type I. Key words: Obesity, Polycystic Ovarian Syndrome.